2021
DOI: 10.1177/00033197211042685
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Clinical Outcomes Following Implantation of LifeStent Self-Expanding Nitinol Stents in Patients With Femoropopliteal Artery Lesions

Abstract: The aim of this study was to evaluate midterm clinical outcomes after implantation of LifeStent self-expanding nitinol stents for the treatment of femoropopliteal lesions. This retrospective, multicenter, non-randomized study examined 260 femoropopliteal lesions in 250 consecutive patients with peripheral artery disease implanted with LifeStents from April 2016 to April 2017. The prevalence of chronic total occlusion (CTO), lesion length ≥25 cm, and distal reference vessel diameter (RVD) <5 mm was 58%, 35%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The scale of the problem of ISR in the endovascular treatment of PAD is well demonstrated by the results of a study conducted by Tan et al The study retrospectively analysed 260 femoropopliteal lesions treated in 250 patients with the implantation of LifeStent selfexpanding nitinol stents. The 3-year restenosis rate for the total population was estimated at 72.9%, and serious limb adverse events were reported in 36.9% [169]. In another study, the outcomes of the endovascular treatment of 481 femoropopliteal lesions with the implantation of InnovaTM self-expanding nitinol stents were analysed in 453 patients.…”
Section: Clinical Significance Of Restenosismentioning
confidence: 99%
“…The scale of the problem of ISR in the endovascular treatment of PAD is well demonstrated by the results of a study conducted by Tan et al The study retrospectively analysed 260 femoropopliteal lesions treated in 250 patients with the implantation of LifeStent selfexpanding nitinol stents. The 3-year restenosis rate for the total population was estimated at 72.9%, and serious limb adverse events were reported in 36.9% [169]. In another study, the outcomes of the endovascular treatment of 481 femoropopliteal lesions with the implantation of InnovaTM self-expanding nitinol stents were analysed in 453 patients.…”
Section: Clinical Significance Of Restenosismentioning
confidence: 99%
“…A significant issue in endovascular revascularization is the comparison of percutaneous transluminal angioplasty with or without stent implantation, for the optimization of treatment in coronary artery disease, atherosclerotic carotid artery disease, and PAD (18). While it is conventionally believed that balloon angioplasty is the safer method for revascularization in PAD, recent studies have also suggested stent implantation as a viable option (19)(20)(21)(22). However, our findings align with the traditional view and demonstrate that stent implantation is an independent risk factor for target vessel restenosis (OR=5.08, P=0.030).…”
Section: Independent Predictors Of Target Vessel Restenosismentioning
confidence: 99%
“…3 In the BEST-CLI, the endovascular techniques applied to CLTI patients included the use of atherectomy (15%), drug-coated balloons (25%) and drugeluting stents (22%). 1 With wider application of advanced endovascular techniques, [4][5][6][7] the outcomes of patients offered endovascular treatment are expected to improve. Thus, the BEST-CLI results may become outdated.…”
mentioning
confidence: 99%
“…As the authors reported, this early increase in reinterventions may have been related to a greater incidence of initial technical failures in the endovascular compared with the surgical group (15 vs 2%, respectively; P < .001). With continuous advances in the endovascular technology, the increased expertise and the wider application of novel devices/techniques, [4][5][6][7] the number of reinterventions in patients offered an endovascular-first approach are expected to decrease.…”
mentioning
confidence: 99%